2005
DOI: 10.1007/s10535-005-3276-3
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of salt stress by low dose γ-irradiation in rice

Abstract: The effects of salt stress on the growth, photosynthesis, and antioxidative ability of the rice (Oryza sativa L.) plants raising from γ-irradiated seeds were investigated using two cultivars, Ilpumbyeo and Sanghaehyanghyella. The 50 and 100 mM NaCl solutions caused a remarkable decrease of the early germination rate and seedling growth. However, the salt stress-induced inhibition of the growth was significantly alleviated in the γ-irradiated plants. The chlorophyll contents and the effective quantum yield of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…With a reverse trend, NPQ in NaClstressed ACC547 was increased by 13.6 and 8.3 % (Table 2), indicating that ACC547 possessed certain mechanisms for the efficient dissipation of excess energy. These results are in agreement with the observations in rice subjected to salt stress as reported by Baek et al (2005). Since zeaxanthin was proposed to be able to dissipate excess excitation as heat in the PS 2 antennae for the first time by Demmig et al (1987), xanthophylls cycle-dependent q E has been extensively accepted as an important mechanism for nonradiative energy dissipation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…With a reverse trend, NPQ in NaClstressed ACC547 was increased by 13.6 and 8.3 % (Table 2), indicating that ACC547 possessed certain mechanisms for the efficient dissipation of excess energy. These results are in agreement with the observations in rice subjected to salt stress as reported by Baek et al (2005). Since zeaxanthin was proposed to be able to dissipate excess excitation as heat in the PS 2 antennae for the first time by Demmig et al (1987), xanthophylls cycle-dependent q E has been extensively accepted as an important mechanism for nonradiative energy dissipation.…”
Section: Resultssupporting
confidence: 92%
“…Some studies have shown that the decrease in photosynthesis is related directly to the salinity-induced stomata closure and the coupled reduction in intercellular CO 2 concentration (Bayuelo-Jiménez et al 2003, Karimi et al 2005. Additionally, salt stress causes the decrease in chlorophyll (Chl) content (Baek et al 2005, Karimi et al 2005, the changes in chloroplast ultrastructure (Stoynova-Bakalova and Toncheva-Panova 2003/4), the depression in photosystem (PS) activity and electron transport (Kirst 1990), and the decline in the activity and content of Rubisco (Ziska et al 1990). All these nonstomatal limitations also make great contribution to the photosynthetic attenuation in salt stressed plants.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effect of drought on growth parameters could be attributed to the osmotic effect of water stress [26,34,35]. Also, the reduction of yield may be ascribed to the harmful effect of soil moisture stress and nutrient balance disorder in root media [36], or reduced rate of new cell production may be make additional contribution to the inhibition of growth [37][38][39]. The reduction in growth criteria due to drought stress might be related to disturbance of water flow from root to shoot [40], decrease in water potential of cell sap [41], or inhibition of cell division [42].…”
Section: Discussionmentioning
confidence: 99%
“…The higher doses of gamma radiation had been found be inhibitory (Radhadevi and Nayar, 1996;Kumari and Singh, 1996), whereas, lower doses may be stimulatory. Low doses of gamma rays have been reported to increase cell proliferation, germination, cell growth, enzyme activity, stress resistance, and crop yields (Charbaji and Nabulsi, 1999;Baek et al, 2005;Chakravarty and Sen, 2001;Kim et al, 2000Kim et al, , 2005. Therefore, this study was aimed to determine the optimum dose of gamma rays for improving shoot, root and survival per cent of strawberry under in vitro conditions.…”
Section: Issn: 2319-7706 Volume 7 Number 03 (2018)mentioning
confidence: 99%